Gestión administrativa en la Empresa “Pentagro S.A” de la ciudad de Babahoyo, periodo 2022. - Guapulema Mariscal, Andrea Stefania (2023)
Introduction: The company “Pentagro S.A” is a company dedicated to the sale and marketing of agricultural inputs. It began in 2019 during the pandemic. Currently, this venture was born as an alternative to the need that arose in the area. agronomic of the Babahoyo canton and why not say of the province of Los Ríos. Pentagro S.A. Identifying the opportunity and an input market that was not very satisfied, he decided to offer agricultural inputs for all types of plantations. Objective: Optimize the productive resources in the company in order to carry out good administrative management of each element that this establishment has. Methodology: the exploratory method was used which helped collect preliminary data, such as interviews, observations or document review, which we could use to design a more focused and specific research approach. Result: the company has great opportunities, the main ones being geographical expansion and commercial agreements since through this it can be seen that the number of dissatisfied customers is many, so that is where the supplies and supplies must be distributed quickly. the service. Conclusion: it was concluded that the situation of the company is good, because, although the weaknesses and threats are greater than the strengths and opportunities, the company must remain in the market looking for the possibility of increasing the value of customer acceptance of the products offered, a criterion that is issued from the theoretical foundation of situational analysis.